MEDYCYNA RATUNKOWATrauma Team – the first personal impressions after the terrorist attacks in Oslo and Utøya - Wilimski, Radosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Out of the 32 patients severely injured in the terrorist attack in the centre of Oslo and on the Utøya island transported to the trauma centre at the Ullevål hospital, 31 were rescued in the first phase, that is crucial for good prognosis. Which factor is responsible for such a good result? Or maybe the success of the rescue operation results from the entity of numerous everyday painstaking efforts of the Trauma Team? The fact of being a specialist in cardiothoracic surgery and the consequent obvious knowledge of the pathophysiology of the respiratory and cardiovascular system makes a cardiothoracic surgeon an important member of the Trauma Team. The tragic events in Norway made me realize that nowadays in any part of the world we can expect the catastrophes, which require urgent optimal medical actions under very tough conditions. Are young Polish cardiothoracic surgeons properly prepared to treat accident victims effectively?